Global Warming: A Very Short Introduction - Maslin M. Mark (New York, Oxford University Press, 2004)
This Very Short Introduction is an up-to-date and readable book about the predicted impacts of global warming and the surprises that could be in store for us in the near future. It unpacks the controversies that surround global warming, drawing on material from the recent report of the Intergovernmental Panel on Climate Change (IPCC), a huge collaborative study that has gathered current thinking on the subject from experts in a range of disciplines. Mark Maslm presents the findings of the Panel for the first time to a general readership and rjscusses the potential climate surprises which the IPCC has not yet had time to assimilate. He ends by discussing the politics of global warming, and looks at what ле can do now to adapt to climate change and mitigate its worst effects.